Asian dust input in the western Philippine Sea: Evidence from radiogenic Sr and Nd isotopes. (17th May 2013) - Jiang, Fuqing; Frank, Martin; Li, Tiegang; Chen, Tian‐Yu; Xu, Zhaokai; Li, Anchun
Abstract: [1] The radiogenic strontium (Sr) and neodymium (Nd) isotope compositions of the detrital fraction of surface and subsurface sediments have been determined to trace sediment provenance and contributions from Asian dust off the east coast of Luzon Islands in the western Philippine Sea. The Sr and Nd isotope compositions have been very homogenous near the east coast of the Luzon Islands during the latest Quaternary yielding relatively least radiogenic Sr ( 87 Sr/ 86 Sr = 0.70453 to 0.70491) and more radiogenic Nd isotope compositions ( ε Nd (0) = +5.3 to +5.5). These isotope compositions are similar to Luzon rocks and show that these sediments were mainly derived from the Luzon Islands. In contrast, the Sr and Nd isotope compositions of sediments on the Benham Rise and in the Philippine Basin are markedly different in that they are characterized by overall more variable and more radiogenic Sr isotope compositions ( 87 Sr/ 86 Sr = 0.70452 to 0.70723) and less radiogenic Nd isotope compositions ( ε Nd (0) = −5.3 to +2.4). The Sr isotope composition in the Huatung Basin is intermediate between those of the east coast of Luzon and Benham Rise, but shows the least radiogenic Nd isotope compositions. The data are consistent with a two end‐member mixing relationship between Luzon volcanic rocks and eolian dust from the Asian continent, which is characterized by highly radiogenic Sr and unradiogenic Nd isotope compositions. The results show that Asian continental dust contributes about 10–50% of the detrital fraction of the sediments on Benham Rise in the western Philippine Sea, which offers the potentials to reconstruct the climatic evolution of eastern Asia from these sediments and compare this information to the records from the central and northern Pacific. Key Points: Sr and Nd isotopic signatures of lithogenic fraction from the Philippine Sea Asian dust input in the western Philippine Sea Offer potentials for reconstructions of the climatic evolution of Asia